CREATIVE THINKING AMONG TODAY’S MUSLIMS: BARRIERS AND BREAKTHROUGHS - Badi, Jamal (Tafakkur, 2007)
Creative thinking and problem solving is of extreme concerns in the Western research for the last half century. The findings of these researches are being implemented and applied in all walks of life: education, administration, leadership, etc. Not only that, it is used in political mobilization, advertisement, propaganda, mind-leading, influencing attitudes through  perceptual manipulation and even as a powerful tool to promote Globalization throughout the whole World. Compared to the above and by looking at the situation in the Muslim World today, we find awkwardness, backwardness, and narrow-mindedness. Many intellectuals who observed such dangerous negative phenomenon raised questions and inquiries. What has happened to the Muslims of today? What are the reasons behind all these traits and qualities? Why Muslims – who are considered as one of the builders of civilizations -are no longer creative and initiative?  How to reactivate creative potential in Muslims so as to revive the vibrant Islamic Thought and reestablish the Islamic Civilization?          This paper aims to explore the external barriers and obstacles that hinder creative thinking among today’s Muslims. Environmental, Educational, and Intellectual barriers will be analyzed and discussed thoroughly. Ways, means and strategies to overcome such barriers will be highlighted. An analytical and critical approach will be used in dealing with issues related to the topic. Both inductive and abductive reasoning will be combined in discussing the above-mentioned barriers. Views of some contemporary Muslim scholars such as Malik Bin Nabi, Iqbal and Abdul Karim Bakkar, to name a few, will be introduced and examined.